2017
DOI: 10.3847/1538-3881/153/1/46
|View full text |Cite
|
Sign up to set email alerts
|

A Survey for New Members of the Taurus Star-Forming Region With the Sloan Digital Sky Survey*

Abstract: Previous studies have found that ∼1deg2 fields surrounding the stellar aggregates in the Taurus star-forming region exhibit a surplus of solar-mass stars relative to denser clusters like IC348 and the Orion Nebula Cluster. To test whether this difference reflects mass segregation in Taurus or a variation in the initial mass function, we have performed a survey for members of Taurus across a large field (∼40 deg 2 ) that was imaged by the Sloan Digital Sky Survey (SDSS). We obtained optical and near-infrared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
144
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(153 citation statements)
references
References 187 publications
8
144
1
Order By: Relevance
“…Two intermediate-gravity objects that Luhman (2006) classified as young field objects are also included; one of the candidates from Gizis et al (1999) was similarly classified by Luhman (2006). While this paper was under review, Luhman et al (2017) reported additional low-mass members; they are not included in our census, but remain as evidence that the Taurus census will continue to grow with the additional of deeper and broader surveys.…”
Section: Sample Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two intermediate-gravity objects that Luhman (2006) classified as young field objects are also included; one of the candidates from Gizis et al (1999) was similarly classified by Luhman (2006). While this paper was under review, Luhman et al (2017) reported additional low-mass members; they are not included in our census, but remain as evidence that the Taurus census will continue to grow with the additional of deeper and broader surveys.…”
Section: Sample Constructionmentioning
confidence: 99%
“…Taurus has long been suggested to have an unusual IMF (Luhman 2000(Luhman , 2004Luhman et al 2009Luhman et al , 2017 Wichmann et al (1996) and Li & Hu (1998), without being confirmed at sufficient confidence to join the established census of Taurus that was promulgated by subsequent works. This trend could have been further exacerbated by the mass-dependent lifetimes of protoplanetary disks (e.g., Carpenter et al 2006).…”
Section: Implications For the Initial Mass Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with several other targets of the same survey, HD 284149 has been proposed to be part of the so-called Taurus-Ext association (Luhman et al 2017;Kraus et al 2017;Daemgen et al 2015), a group of stars with similar space position and kinematics of the Taurus star forming region but distinctly older ages. A dedicated age estimate was then performed for HD 284149 by Bonavita et al (2014), using several youth indicators, leading to an adopted age of 25 +25 −10 Myrs.…”
Section: Introductionmentioning
confidence: 99%
“…The Taurus and Perseus star-forming regions are two of the most appealing targets for a brown dwarf survey because of their proximity (d = 140 and 300 pc; Torres et al 2012;Schlafly et al 2014, references therein) and the relatively large sizes of their stellar populations (N∼400 and 800, Kenyon et al 2008;Bally et al 2008). Luhman et al (2016Luhman et al ( , 2017 have provided recent summaries of previous surveys for members of Taurus and the two richest clusters in Perseus, IC 348 and NGC 1333 (see also Kraus et al (2017) for Taurus). The census of each region contains several dozen objects with spectral types indicative of brown dwarfs (>M6), most of which were identified with optical and infrared (IR) photometry.…”
Section: Introductionmentioning
confidence: 99%